Serum levels of per- and polyfluoroalkyl substances alternatives and blood pressure by sex status: Isomers of C8 health project in China. (December 2020) - Mi, Xin; Yang, Yun-Qing; Zeeshan, Mohammed; Wang, Zhi-Bin; Zeng, Xiao-Yun; Zhou, Yang; Yang, Bo-Yi; Hu, Li-Wen; Yu, Hong-Yao; Zeng, Xiao-Wen; Liu, Ru-Qing; Dong, Guang-Hui
Abstract: Several in vitro and in vivo studies have demonstrated the toxicity of perfluoroalkyl and polyfluoroalkyl substances (PFASs) alternatives, however, relevant epidemiological findings remain to be performed. In addition, the association between PFASs alternatives and blood pressure has not been explored. To address this gap, we quantified serum levels of alternatives and legacy PFAS in 1273 healthy Chinese, aged 34–94 years, from "isomers of C8 health project". Our results showed that an increase of serum PFASs levels was correlated with elevated blood pressure and higher prevalence of hypertension: per natural log unit (ng/mL) increase of 6:2 chlorinated polyfluorinated ether sulfonic acids (Cl-PFESA) elevated 1.31 (95%CI: 0.13, 2.50) mmHg of diastolic pressure (DBP). Adjusted odds ratios (aORs) for hypertension with per natural log increase of 6:2 and 8:2 Cl-PFESA were 2.57 (95%CI: 1.86, 3.56) and 1.18 (95%CI: 1.06, 1.32), respectively. When stratified by sex, the effects of PFASs alternatives on increased blood pressure and hypertension were stronger in women. Meanwhile, the association between 6:2 Cl-PFESA (aOR = 6.81; 95%CI: 3.54, 13.09) and hypertension was stronger than perfluorooctanoic acid (PFOA) (aOR = 2.32, 95%CI: 1.38, 3.91) in women. In conclusion, our pilot study demonstrates that serum concentrations of PFASs alternatives are positively associated with blood pressure. Moreover, women seem to be more susceptible, and alternatives exhibited stronger effects than legacy PFASs. Graphical abstract: Image 1 Highlights: A large population-based study was conducted to assess associations between PFASs alternatives exposure and blood pressure. Exposure to PFASs alternatives increases the estimates of blood pressure and the odds ratio of hypertension. PFASs alternatives exhibit stronger effects than legacy PFASs on blood pressure, and women are at greater health risk.